Disney's Lilo & Stitch - Ehrbar, Greg; Narciso, Massimiliano (New York : Disney Press, 2002)
"When Lilo adopts a pet dog named Stitch, she doesn't realize that he is actually an alien experiment! Soon she and Stitch are causing worlds of trouble and having tons of fun"--Back cover.
Keywords: Human-alien encounters -- Comic books, strips, etc -- Juvenile fiction; Human-alien encounters -- Comic books, strips, etc; Hawaii -- Comic books, strips, etc -- Juvenile fiction; Hawaii -- Comic books, strips, etc; Graphic novels